Speech Recognition Robot using Endpoint Detection Algorithm - Prasanna Kumar M (International Journal of Engineering and Management Research, 2022)
Controlling the machines and environment with speech makes human life easier and comfortable. In this direction a robot has been designed which can easily be controlled through the speech commands given by an authorised person. This work consists of two phases: Speech recognition and Robot control. Voice commands are given as an input, which is processed using the LabVIEW software. Speech processing is done using two algorithms: Endpoint detection algorithm and Silence removal algorithm. These algorithms differentiate the voice signal from the background noise, detect the word boundary and extract only the voiced part of the input signal and removing the background noise associated with it. The extracted voice command signal is then matched with the stored templates and on match, the code corresponding to a particular movement of robot is encoded and then transmitted to the robot controlling module via RF transmitter. RF receiver in robot controlling module receives the transmitted signal, which is decoded and applied as an input to microcontroller. The microcontroller interprets the code and initiates the robot movement depending on the command given. By giving proper command, robot can be made to stop, move forward, backward, turn left, turn right etc., This robot can be deployed in hazardous environment and can be controlled by an authorised person. It may also assist disabled people to carry out their daily work with ease.